Evaluation of financial behaviour in Malaysia : evidence from undergarduates students of Universiti Teknologi MARA Perlis / Norsyamimi Tahir - Tahir, Norsyamimi
Financial behavior plays an important role in influencing the welfare of individuals in a household, society, nation and the world at large. Economics literature suggests that any individual will take into consideration all available information to make choices that maximize their utility, profit and wellbeing. It is generally assumed any individuals have an unlimited ability to process information that will enable them to make well-informed choices. The main objective of this study is to investigate the determinants of financial behavior of university students. This research will also examine whether financial behavior of these students differ by financial literacy level. Data will be gathered via questionnaires that included personal information, financial attitude, financial behavior, factors influences their decision and financial knowledge.